Rethinking urban form in a shrinking Arctic city - Gunko, Maria; Batunova, Elena; Medvedev, Andrey (Université des Sciences et Technologies de Lille, 2021)
Shrinking cities – places which need to ‘narrow down’ the too spacious settings – pose challenges to the mainstream urban planning which naturalizes growth and direct approaches advocating it. While shrinking cities are located worldwide, responses to the phenomenon are place-specific depending on the knowledge and resources of decision-makers, as well as the discourses of the desired spatial development. In this sense, it is still not precisely clear why and how urban planning changes under conditions of shrinkage. Since the beginning of the 1990s, many Russian cities began to lose population. Excluding the oil and gas provinces, the Russian Arctic has become a ‘showcase’ of the country’s population exodus. Our contribution is based on empirical evidence from Vorkuta (Komi Republic, Russia) an Arctic city with around 54 thousand people which is among the fastest shrinking cities of the country. Due to the simultaneous need for improving housing conditions, dealing with negative physical effects of shrinkage, and high maintenance costs of housing and infrastructure the local stakeholders had to come up with a new approach toward planning – the so-called ‘controlled shrinkage’ that helped reduce sprawl and fragmentation. Les villes en décroissance – soit des lieux qui nécessitent de ‘réduire’ leur vaste cadre - posent des défis à l'urbanisme général qui vise normalement à la croissance, et aux approches directes qui la préconisent. Bien que les villes en déclin se trouvent dans le monde entier, les réponses à ce phénomène sont spécifiques à chaque lieu en fonction des connaissances et des ressources des décideurs, ainsi que des discours sur le développement spatial souhaité. En ce sens, on ne sait pas encore exactement pourquoi et comment l'urbanisme évolue dans des conditions de rétrécissement. Depuis le début des années 1990, de nombreuses villes russes ont commencé à perdre de la population. À l'exception des provinces pétrolières et gazières, l'Arctique russe est devenu une ‘vitrine’ de l'exode de la ...